EIF Private Debt Survey 2021: Private debt for SMEs - Market overview - Helmut Krämer-Eis; Jörn Block; Antonia Botsari; Carlos Krause; Salome Gvetadze; Alexandra Moritz; Frank Lang; Anna Schulze (European Investment Fund (EIF), 2022)
Against the background of the need for alternative and additional financing channels for SMEs in Europe, this paper analyses the market segment of debt funds. It provides a market overview and comprehensive insight into the results of the EIF Private Debt Survey, a new study that provides unique perspective and helps to increase the transparency of the market to the public. Finally, the paper presents the EIF's action plan to address market weaknesses in the European private debt market.
Keywords: 330